Blood cell indices as predictors of complicated appendicitis: A diagnostic study - Julio César Moreno-Alfonso; Ada Molina Caballero; María Concepción Yárnoz Irazábal; Alberto Pérez Martínez (Elsevier, 2023)
Background: Appendicitis in children is associated with diagnostic complexity leading to delayed diagnosis. Such delays risk progression to complicated appendicitis. This study investigates the potential of cellular indices, including neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), to differentiate uncomplicated (UA) from complicated appendicitis (CA). Methods: Diagnostic study of pediatric patients with acute appendicitis admitted to our hospital from 2021 to 2022. NLR, dNLR, PLR and MLR were compared between groups. Results: A total of 182 patients were enrolled: 116 cases with CA (63 % male, age 9.6 ± 5.5 years) and 66 patients with UA (67 % male, age 10.6 ± 2.7 years). All blood cell indices were significantly higher in the CA group than in the UA group (p= <0.0001). NLR, dNLR and PLR have a good area under the receiver operating characteristic (ROC) curve, whereas MLR has a regular curve (0.735). PLR was the most accurate predictor of CA with a sensitivity of 60 %, specificity of 85 %, positive predictive value of 88 %, area under the ROC curve of 0.802 (95 % CI 0.737-0.866) and a cut-off point for the diagnosis of CA of 213.3. The post-test probability of CA for a positive result on PLR was 80 % (95 % CI 69-88). Conclusions: PLR seems to be the most accurate cellular index to differentiate uncomplicated from complicated appendicitis in children. It may be useful for prioritizing cases for surgery as a predictor of intraoperative findings and early postoperative courses.